Translation, Cultural Adaptation and Validation of Cardiff Acne Disability Index in Nepali Language - Paudel, Sushil; Parajuli, Niraj; Shrestha, Shraddha; Hirachan, Shashi (Journal of Nepal Health Research Council, 2023)
Background: Acne causes significant impairment in the quality of life of patients, but clinicians in Nepal lack a simple validated tool to measure the psychological side of acne. We planned to translate and validate Cardiff Acne Disability Index, a five item questionnaire into Nepali language to address this need. Methods: A linguistic translation with semantic equivalence to the original English language Cardiff Acne Disability Index was achieved through standard forward and backward translation into Nepali language. All eligible patients were requested to fill the Nepali translated version of both Cardiff Acne Disability Index and Dermatology Life Quality Index questionnaires. Reliability and validity of the newly translated questionnaire were established, based on statistical analyses of factor structure, item correlations and concurrent correlations. Results: This validity study included 94 patients with male: female ratio of 1:3.27 and mean age 21.29 (±3.92) years. Reliability analysis revealed a Cronbach’s alpha of .72 and mean inter item correlation coefficient of .337. A single factor was extracted on Principal Component Analysis explaining 48.40% of variance. A strong correlation of Cardiff Acne Disability Index scores to the Dermatology Life quality Index score (rs>.7) indicated good concurrent validity. Conclusions: The newly translated Nepali Cardiff Acne Disability Index is a valid tool to measure the impact of acne in Nepalese patients. This short and simple assessment tool will help clinicians understand the patient’s perspective of her acne. Keywords: Acne; cardiff acne disability index; quality of life; validity.